2002
DOI: 10.1046/j.1365-2761.2002.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental susceptibility of different life‐stages of the giant freshwater prawn, Macrobrachium rosenbergii (de Man), to white spot syndrome virus (WSSV)

Abstract: Studies were conducted by injecting/feeding white spot syndrome virus (WSSV) derived from infected shrimp, Penaeus monodon (Fabricius), to different life‐stages, namely post‐larvae, juveniles, sub‐adults and adults of Macrobrachium rosenbergii (de Man). The disease was also induced in brood stock, and the eggs and larvae derived from these animals were subsequently tested for WSSV infection. All the stages except egg used for the experiment were found WSSV positive in histopathology, cross infection bioassay a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Immediately following ecdysis, the new exoskeleton is soft and the exercise capacity of shrimp is very weak, so post-molt (P1) is the most sensitive period to suffer an attack from bacteria, viruses, or other predation. It is known that shrimp practice cannibalism which can abet the outbreak of infectious diseases such as White Spot Syndrome (WSS) [ 68 ] and the targets of cannibalism are mainly post-molt shrimp. The immune and protection tactics that allow post-molt shrimp to avoid stress are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately following ecdysis, the new exoskeleton is soft and the exercise capacity of shrimp is very weak, so post-molt (P1) is the most sensitive period to suffer an attack from bacteria, viruses, or other predation. It is known that shrimp practice cannibalism which can abet the outbreak of infectious diseases such as White Spot Syndrome (WSS) [ 68 ] and the targets of cannibalism are mainly post-molt shrimp. The immune and protection tactics that allow post-molt shrimp to avoid stress are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated differential susceptibility between age cohorts of the same host species, normally in the context of aquaculture, whereby early age classes (such as eggs and larvae) can be afflicted by different diseases (or the same diseases at a different prevalence and severity) to those observed in adult life stages (e.g. Kiran et al 2002, Bergmann et al 2003. This concept provides a rationale to consider whether similar phenomena may be apparent in natural (wild) populations of aquatic animals and furthermore, whether differential age of onset for the same disease may occur across geographical regions or temporally.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on WSSV pathogenicity for juveniles and adults of M. idella, M. lamerrae, and M. rosenbergii indicated that M. idella and M. lamerrae are more susceptible to WSSV infections compared to M. rosenbergii, which has a high level of tolerance [12]. A study by Kiran et al [16] also showed that earlier growth stages of M. rosenbergii are more susceptible to WSSV infections compared to their sub-adult and adult stages wherein they are more tolerant to infection by this virus.…”
Section: Introductionmentioning
confidence: 99%